IMPLEMENTASI MODEL KURIKULUM INTEGRATIF DI PONDOK PESANTREN AL-KAMIL CIANJUR - Supriyadi, Asep (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
One of the problems that occurs in the world of Islamic boarding schools is adaptation to the times. Meanwhile, the times are constantly changing and need to be followed, but still within the frame of the santri tradition that upholds the morals of karimah. The purpose of this article is to find an integrative model of education in islamic boarding schools. The method used in this study was a qualitative approach, data collection techniques through observation, interviews and documentation at the research locus located at the Al-Kamil Cianjur Islamic Boarding School. The results of the study showed that the integration of the curriculum in the Pondok pesantren Al-Kamil Cianjur was by integrating the pesantren curriculum, namely Dirasah Islamiyah, the study of the yellow book and the National curriculum. Dirasah Islamiyah consists of 8 subjects namely: Arabic, Aqidah, Shorof, Nahwu, Fiqih, Siroh, Tajwid, Adab &Akhlaq. The national curriculum consists of the curriculum for junior and senior high school education levels. The junior high school curriculum consists of 8 subjects, namely: Indonesian, PAI, Mathematics, English, Science, Social Studies, PKN, Pjok. While consisting of 16 subjects, namely: PAI, PPKn, Indonesian, Mathematics, History, English, PJOK, Biology, Physics, Chemistry, Geography, Sociology, Economics, Informatics, Sociology, Art Crafts. All of these subjects, both Dirasah Islamiyah, the national curriculum is carried out integratively in the time range of 03.00-22.00 WIB. The contribution of this article gives an idea that islamic boarding schools have room for the development of integrative education that is able to adapt to the conditions of the times.